Antioxidant vitamins (A, C and E) and malondialdehyde levels in acute exacerbation and stable periods of patients with chronic obstructive pulmonary disease - Tug, T; Karatas, F; Terzi, SM (Canadian Soc Clinical Investigation, 2004)
Background: People with chronic obstructive pulmonary disease (COPD) undergo oxidative damage during exacerbations that continues in stable periods, gradually contributing to pathogenesis. Since serum concentrations of antioxidant vitamins in COPD patients have been little investigated, we studied antioxidant vitamin and lipid peroxidation concentrations in patients during acute exacerbations and stable periods. Methods: We prospectively recruited 24 patients with COPD (mean age 51.8 yr, standard deviation [SD] 6.7 yr) in acute exacerbation. Serum concentrations of vitamins A, C and E and malondialdehyde (MDA) were determined before treatment and during stable periods with high-performance liquid chromatography, and in 23 healthy controls (mean age 48.0 yr; SD 5.9 yr) with established methods. Results: The mean vitamin A level in patients during acute exacerbation was 0.8 (SD 0.2) mug/mL, rising to 1.0 (SD 0.2) mug/mL during stable periods, both significantly less than that of controls (1.0 [SD 0.2] mug/mL; p < 0.01); vitamin C, 5.0 (SD 2.2) mug/mL acute and 7.5 (SD 2.7) stable, neither significantly differing from the mean level in controls (8.6 [SD 1.8] mug/mL; p > 0.05); vitamin E, 10.0 (SD 2.4) mug/mL acute and 11.1 (SD 2.6) stable, both lower than in controls (11.0 [SD 2.86] mug/mL; p < 0.01); and MDA, 2.4 (SD 0.7) nmol/mL acute and 1.2 (SD 0.4) stable, both higher than in controls (0.9 [SD 0.2] nmol/mL; p < 0.01). Conclusions: Whereas patients with COPD undergo increased oxidative stress during exacerbations and in stable periods, their serum concentrations of antioxidant vitamins A and E decrease during exacerbations. Our findings suggest that the administration of vitamins A and E may be beneficial in the prevention and treatment of the harmful effects of COPD. (C) 2004 Canadian Medical Association.
Keywords: Induced Lipid-Peroxidation; Lung-Function; Rheumatoid-Arthritis; Oxidative Stress; Rat Erythrocytes; Serum; Oxidants; Smokers; System; Damage